Pengaruh Pembuatan Ecobrick Terhadap Tingkat Kepedulian Lingkungan pada STIE TN Dumai - Lis Hafrida; Mufti Hasan Alfani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
Plastic waste is a problem that has not been resolved to date, meanwhile with an increase in the population will also follow the increase in the volume of waste generation generated from human activities. Other alternatives are needed to handle the volume of plastic waste in the Dumai City environment such as making ecobricks. This research is intended to see the relationship between plastic waste processing and ecobrick manufacturing on the level of environmental awareness for Dumie STIE-TN students using simple linear regression analysis with the help of SPSS version 24. From the results of simple linear regression it can be concluded that making ecobrick has a positive regression coefficient. This shows that the making of ecobrick, has a positive influence on the level of environmental concern for students of STIE-TN Dumai. Keywords: Ecobrick, Plastic Waste, Environment